Diversity of Orthoptera at Bukit Ulu Piah, Tambun, Perak, Peninsular Malaysia - Saupi, Nur Atiqah; Sulaiman, Azman; Hazmi, Izfa Riza; Muhammad Nasir, Dzulhelmi; Angeline D.D.,; Abdullah, Nur Athirah; Shamsir, Rabiatul Addawiyah; Wan Mohd Nor, Wan Nurul ‘Ain (Malaysian Journal of Science, 2025)
Orthoptera carries important role in maintaining the ecosystem thus are diversely distributed and have over 29,100 described species worldwide. No such description has ever been reported in Bukit Ulu Piah, Tambun, Perak, ergo this study is conducted to identify the diversity of Orthoptera and to provide the first Orthoptera species checklist of the area. Net sweeping sampling was executed from January to April 2022, between 0900 a.m. until 1700 p.m. The species abundancy data were analyzed using PAST software to determine the Shannon diversity index (H’), Margalef index (Dmg), and Evenness index (E). Accumulation of 508 specimens from six families of Acrididae, Pyrogomorphidae, Chorotypidae, Tetrigidae, Gryllidae, and Tettigoniidae were successfully recorded with Acrididae noted the highest percentage value of 39.5% (15 species). Species composition break apart into 38 species in 32 genera with two Suborder Caelifera (21 species) and suborder Ensifera (17 species). Melanoplus sp. was the common and most abundant species with a total of 59 individuals (11.6% of total specimens). Orthoptera diversity in Bukit Ulu Piah, Tambun records a high diversity (H’= 3.037), a high species richness (Dmg = 5.939) and uniform species evenness (E = 0.5487). The one-way ANOVA in duration of four months of Orthoptera sampling indicates no difference (p = 0.4316; p > 0.05). However, a significance t-test value between S1 and S2 as well as between S2 and S4, with p = 0.0282 and p = 0.014, respectively is due to human activities of grass-mowing and pest control. In conclusion, our first species checklist will provide preliminary information for references in upcoming research and contributes to achieving the goal of the National Biodiversity Policy 2025.